Multipotential use of an old drug, as a new solution for anticancer therapy and multidrug-resistant urinary tract infections - Patryk Banaś; Kamila Abram; Justyna Adamus; Jakub Rafał Pierzchała; Katarzyna Bednarz; Natalia Sobańska; Aleksandra Paulina Banasiak; Rafał Teichman; Jakub Kasprowicz; Michał Hyjek (Journal of Education, Health and Sport, 2023)
Introduction